CHRONIC THROMBOEMBOLIC PULMONARY HYPERTENSION: HOW TO DIAGNOSE? A CASE REPORT - Sidhi Laksono; Hillary Kusharsamita (Berkala Ilmiah Kedokteran Duta Wacana, 2023)
Background Chronic thromboembolic pulmonary hypertension (CTEPH) is a pulmonary embolism (PE) complication that is a primary cause of pulmonary hypertension (PH) and may lead to right heart failure and significant mortality especially when left untreated. Although CTEPH is the only cause of PH that is curable without needing to resort to lung transplant, it is often misdiagnosed due to the absence of diagnostic instruments and the absence of specific presenting symptoms. This also complicates the process of distinguishing between acute thromboembolic disease and the acute embolic event worsening of undiscovered CTEPH. Objective A better understanding of CTEPH is crucial, therefore we discuss a diagnosis rare case of CTEPH. Case Description A 44-year-old man presenting with syncope and chest discomfort who had no previous episodes of acute PE. Conclusion Computed Tomography Pulmonary Angiography (CTPA) is a significant test for identifying CTPEH. Oral anticoagulants may provide patients with CTEPH a safe and beneficial life-long treatment.